2011
DOI: 10.19030/jabr.v21i3.1468
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Country-Of-Origin Effects: The Impact Of An International Event

Abstract: <p class="MsoNormal" style="text-justify: inter-ideograph; text-align: justify; margin: 0in 0.6in 0pt 0.5in;"><span style="font-size: 10pt; mso-bidi-font-style: italic;"><span style="font-family: Times New Roman;">This study is to investigate how consumers&rsquo; attitudes toward brands/products manufactured by a country are affected by an international event. Authors explored that consumers&rsquo; attitudes toward brand &ldquo;made in ___&rdquo; are affected by various constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…По мере экономического роста и повышения международной конкурентоспособности Китая отмечается позитивное восприятие у больших групп покупателей развитых стран «Made in China» как бренда [Kauf, Tłuczak, 2016], что, вероятно, во многих случаях имеет отношение к гибридным продуктам. Еще одна попытка представить бренд «Made in…» показывает, что отношение потребителя к нему определяется такими конструктами, как предшествующие представления об атрибутах продуктов, образ страны и имя бренда [Cho, Ha, 2005]. Все это свидетельствует как о неопределенности попыток концептуализации бренда «Made in …», так и о его тесной связи с СОО-эффектами и брендом страны.…”
Section: «сделано в россии» как национальный брендunclassified
“…По мере экономического роста и повышения международной конкурентоспособности Китая отмечается позитивное восприятие у больших групп покупателей развитых стран «Made in China» как бренда [Kauf, Tłuczak, 2016], что, вероятно, во многих случаях имеет отношение к гибридным продуктам. Еще одна попытка представить бренд «Made in…» показывает, что отношение потребителя к нему определяется такими конструктами, как предшествующие представления об атрибутах продуктов, образ страны и имя бренда [Cho, Ha, 2005]. Все это свидетельствует как о неопределенности попыток концептуализации бренда «Made in …», так и о его тесной связи с СОО-эффектами и брендом страны.…”
Section: «сделано в россии» как национальный брендunclassified
“…promoted via sporting events, films, TV shows, and any other marketing promotional campaigns help enhance the image of a country. Previous studies (Cho and Ha 2005) explored that consumer attitudes toward a brand "made in ___" are affected by various constructs, such as the country's image along with the brand name, and attitudes toward the advertising during an international event. A study by Cho and Ha (2005) also found that the impact of marketing campaigns during and international event such as World Cup significantly affect customers' belief of the brand and the country simultaneously.…”
Section: Image Of Countrymentioning
confidence: 99%
“…Previous studies (Cho and Ha 2005) explored that consumer attitudes toward a brand "made in ___" are affected by various constructs, such as the country's image along with the brand name, and attitudes toward the advertising during an international event. A study by Cho and Ha (2005) also found that the impact of marketing campaigns during and international event such as World Cup significantly affect customers' belief of the brand and the country simultaneously. Studies also addressed that the impact of different degrees of recall regarding how advertising during an international event affects consumers' attitudes toward the brands, as well as how advertising by different media affects attitudes toward the brand.…”
Section: Image Of Countrymentioning
confidence: 99%